Demographic, Seasonal, and Geographic Differences in Emergency Department Visits for Epistaxis. (January 2017) - Chaaban, Mohamad R.; Zhang, Dong; Resto, Vicente; Goodwin, James S.
Objective: To determine the demographics and seasonal and geographic variation of epistaxis in the United States. Study Design: Retrospective cohort analysis based on data from Medicare claims. Setting: Emergency department visits. Subjects and Methods: We used a 5% sample of Medicare data from January 2012 to December 2012. Our cohort included patients with an incident diagnosis of epistaxis during a visit to the emergency department, excluding those with a diagnosis in the prior 12 months. Demographics included age, sex, race, and ethnicity. We compared the rate of emergency department visits for epistaxis by geographic division and individual states. Results: In the 5% sample of Medicare data, 4120 emergency department visits for incident epistaxis were identified in 2012. Our results showed an increase in the emergency department visits for epistaxis with age. Compared with patients <65 years old, patients who were 66 to 76, 76 to 85, and >85 years old were 1.36 (95% confidence interval [95% CI], 1.23-1.50), 2.37 (95% CI, 2.14-2.62), and 3.24 (95% CI, 2.91-3.62) more likely to present with epistaxis, respectively. Men were 1.24 (95% CI, 1.17-1.32) times more likely to present with epistaxis than women. Blacks were 1.23 (95% CI, 1.10-1.36) times more likely to present with epistaxis when compared with non-Hispanic whites. Epistaxis emergency department visits were 40% lower in the summer months versus winter. The seasonal variation was more pronounced in the northern versus southern United States. Conclusion: Emergency department visits for epistaxis increase with age and appear to be seasonal, with a more pronounced variation in the northern versus southern United States.